Analisis Penatagunaan Sumber Daya Air (Studi Kasus Kabupaten Kotabaru Darat) - Hidayat, Muhammad Rezki; Ridhani, Muhammad Yusuf (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Tanjungpura, 2024)
Abstrak: Air merupakan sumber kehidupan di bumi ini. Air yang ada dibumi ini tidak hanya dibutuhkan oleh manusia tetapi juga oleh alam guna menjaga stabilitas ekosistemnya. Keberadaan air dalam kuantitas, kualitas dan waktu tertentu sangat diharapkan guna menjamin kelestarian hidup manusia dan lingkungan. Namun semakin meningkatnya jumlah manusia, semakin berkembangnya daerah pertanian dan pemukiman, serta menurunnya daerah resapan, kualitas lingkungan dan berubahnya pola cuaca, maka mulai dirasa ketidakseimbangan antara pemanfaatan dan ketersediaan air dalam jumlah dan kualitas yang mencukupi. Kata kunci: Air, Ketersediaan, Kebutuhan . Abstract: Water is the source of life on this earth. Water on earth is not only needed by humans but also by nature to maintain the stability of its ecosystem. The existence of water in a certain quantity, quality and time is highly desirable to ensure the preservation of human life and the environment. However, as the number of people increases, the development of agricultural and residential areas, as well as the decline in catchment areas, environmental quality and changes in weather patterns, there is an imbalance between the use and availability of water in sufficient quantity and quality.Keywords: water, availability, need.